Effect of Short Term Sibutramine Supplementation on Appetite Suppression and Related Metabolic Responses - Swati Jain; Saroj K. Verma; Vijay K. Singh; Som Nath Singh (Journal of Pharmacy and Nutrition Sciences, 2012)
The appetite suppressing property of Sibutramine is well reported. The present study was undertaken to investigate the appetite regulatory mechanism and associated metabolic changes induced in male Sprague Dawley rats by its short term supplementation. The effect of the drug on the regulatory hormones and biochemical variables was studied at an oral dose of 10 mg/kg body weight. There was a decrease in food intake of rats by 35.5% in comparison to their basal food intake as well as untreated controls. There was an increase in plasma levels of adiponectin, serotonin and a decrease in IGF-1 and corticosterone in the treated animals. The circulating levels of ghrelin marginally decreased with a corresponding increase in leptin and CCK in case of treated rats. These may be responsible for the anorectic effect of the drug.